Comparative study of pathological lesions of liver in autopsy cases - Simon, K. Ankita; Dantkale, Sunita; Shinde, Samruddhi (International Journal of Research in Medical Sciences, 2020)
Background: Liver is a site for plethora of diseases among which many become symptomatic while others usually either go undiagnosed or are concealed by other prominent diseases. As said about liver to be the custodian of milieu interior most of the silent liver diseases are diagnosed only on autopsy examination. Aims and objectives was to study various pathological lesions of liver in medicolegal and clinical autopsy cases and to corelate liver diseases with age and sex. Retrospective cross-sectional observational study of 649 medicolegal and clinical autopsies conducted within 2 years of duration (January 2017 to December 2018). Methods: Out of all 649 autopsies conducted in our hospital all liver specimens along with other organs viscera were collected and formalin fixed. After gross examination sections from the liver were submitted for tissue processing and then stained with haematoxylin and eosin stain. Results: The most common pathology found in our study was fatty change (11.1%) followed by venous congestion (4.3%), hepatitis (3.5%), cirrhosis (2.2%), tuberculosis/ granulomatous hepatitis (0.6%), chronic hepatitis (0.3%), malignancy (1%), miscellaneous (2%) and normal (72.4%). Maximum cases were in 21-30 years of age group with male preponderance. Conclusions: Autopsy examination of liver is an effective tool to identify silent liver diseases. Use of autopsy findings along with other investigative techniques.